Phosphatidic acid production on the vacuole harboring Legionella pneumophila is a signal for recognition of interferon-induced GTPases - Hiromu Oide; Tomoko Kubori; Hiroki Nagai; Takashi Nozawa; Ichiro Nakagawa; Miwa Sasai; Masahiro Yamamoto; Kohei Arasaki (Proceedings of the National Academy of Sciences, 2025)
The interferon (IFN)-inducible GTPases play a crucial role in cell autonomous immunity against intracellular pathogens. Particularly, these GTPases directly recognize the host membrane-derived vacuole containing pathogens and subsequently destroy it. Although it has been revealed that these GTPases target the membrane of Legionella pneumophila ( L. pneumophila )-containing vacuole (LCV), molecular mechanism has been totally uncleared. Here, we show that mouse guanylate-binding protein 2 (mGBP2) is specifically recruited to the LCV and subsequently ruptures it. Furthermore, we also show that mGBP2 recognizes phosphatidic acid (PA) produced by the Legionella effector Lpg2552 and fails to target the vacuole harboring Lpg2552-depleted L. pneumophila . Consistently, this strain successfully grows in cells expressing mGBP2. We additionally identified lysine 585 (K585) of mGBP2 is required for the binding to PA and K585-mutated mGBP2 fails to recognize LCV. Interestingly, this lysine residue is only conserved in GBP1 among human GBPs and the conserved lysine residue is important for PA recognition and subsequent LCV distribution. Importantly, L. pneumophila lacking Lpg2552 exhibits high resistance against IFN stimulation in THP-1-derived human macrophage.